2006
DOI: 10.1186/1745-0179-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ObjectiveTo measure the effectiveness of manualized cognitive-behavioural group therapy (CBGT) when it is integrated into the routine care on a general hospital psychiatric inpatient unit.MethodsA pre-post design is used to measure the "process", "results" and "outcome" indicators in the year before CBGT was introduced (2001) in contrast to the subsequent two years (2002, 2003). Readmission to hospital, compulsory admissions, ward atmosphere (i.e. the use of physical restraint, episodes of violent behaviour) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…This demonstrates that a policy to reduce coercive interventions should aim at different targets – not only training, culture, and attitudes can be a successful strategy, but also focusing on the needs of different groups of patients. There is some evidence that systematic implementation of psychotherapeutic elements such as groups with cognitive-behavioural therapy or relationship management therapy can help to reduce coercive interventions [ 18 , 19 ]. In contrast to such interventions described before, we did not introduce single psychotherapeutic interventions but a different organisational structure as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that a policy to reduce coercive interventions should aim at different targets – not only training, culture, and attitudes can be a successful strategy, but also focusing on the needs of different groups of patients. There is some evidence that systematic implementation of psychotherapeutic elements such as groups with cognitive-behavioural therapy or relationship management therapy can help to reduce coercive interventions [ 18 , 19 ]. In contrast to such interventions described before, we did not introduce single psychotherapeutic interventions but a different organisational structure as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of coercion as response to aggression underscores the need for research on preventive or less restrictive interventions vis-à-vis aggressive behaviour (see e.g. [ 46 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Lauriello Lauriello and Pallanti (2012) suggested that family space needed members who participate in family psychoeducational programs experience lower levels of subjective burden, improved life satisfaction and acquire greater knowledge, hope and empowerment. Interventions should be patient-oriented and facilitated by trained personnel (Veltro et al 2006). Here patients are taught how to recognize events and situations that may be highly stressful, highlighting early-warning signs of stress overload and impending recurrences.…”
Section: Introductionmentioning
confidence: 99%